Curating Ethnomusicology in Cyberworlds for Ethnomusicological Research: World Music in Wonderland - Frishkopf, Michael; Cohen, Michael; Ranaweera, Rasika (Ethnologies, 2015)
We describe a musical cyberworld as a virtual space for curating ethnomusicology, as well as for conducting research: the ethnomusicology of controlled musical cyberspaces. Our cyberworld differs from most online music curation in enabling immersive, social experience. Considering such cyber-exhibition of ethnomusicological research as itself a form of social and musical practice also calls for an ethnomusicology of such exhibits. Research in ethnomusicology has typically been conducted through qualitative fieldwork in uncontrolled settings. By contrast, we design a custom musical cyberworld as a virtual ethnomusicological laboratory, a platform for research geared towards better ways of designing online musical exhibitions for discovery, learning, and aesthetic contemplation, as well as contributing towards our general understanding of the role of music in human interaction and community formation.